Investing U.S. Social Security Trust Fund Assets in Private Securities - Leidy, Michael (IMF Working Papers; Working Paper ;, 1997)
This paper examines the macroeconomic and distributional consequences of a policy change, other things being equal, that would allow U.S. Social Security trust fund assets to be invested in private securities. Improving the expected return to trust fund assets, by shifting these from government bonds to private securities, tends to reduce (increase) the future claim on national output of the current (future) working population. The effects on aggregate saving and future output depend on whether current workers interpret this policy change as affecting their future Social Security benefits.